Effects of exogenous N-acyl-homoserine lactones on nutrient removal, sludge properties and microbial community structures during activated sludge process. (September 2020) - Yan, Xu; Zheng, Shikan; Huo, Zhaoman; Shi, Bowen; Huang, Jiajun; Yang, Jie; Ma, Jiahui; Han, Yunping; Wang, Yan; Cheng, Ke; Feng, Jinglan; Sun, Jianhui
Abstract: This study investigated the effects of exogenous N-acyl-homoserine lactone (AHL) signal molecules, N-hexanoyl-l -homoserine lactone (C6-HSL) and N-octanoyl-l -homoserine lactone (C8-HSL), on treatment performance, sludge properties and microbial community structures in activated sludge systems. Results showed that the nitrification and denitrification efficiencies were enhanced with the addition of signal molecules. The particle size, irregularity, and internal mass transfer resistance of activated sludge flocs (ASFs) increased, primarily because dosing AHLs led to a content increase and chemical composition variation of extracellular polymeric substances (EPS) in sludge. Microbial analysis indicated an increase in both the bacterial richness and diversity of the systems. The relative abundances of the key functional groups, including bacteria related to C and N removal and EPS production, varied correspondingly. This study presents an insight into the comprehensive understanding of the effects of AHL-based quorum sensing on activated sludge treatment process. Graphical abstract: Image 1 Highlights: AHLs enhanced the nitrification and denitrification efficiencies. AHLs increased the particle size, irregularity and internal mass transfer resistance of ASFs. AHLs influenced the content and chemical composition of EPS in sludge. Bacterial functional groups involved C and N removal, and EPS production correlated with AHLs.